Saccharomyces cerevisiae GATA Sequences Function as TATA Elements during Nitrogen Catabolite Repression and When Gln3p Is Excluded from the Nucleus by Overproduction of Ure2p() - Cox, Kathleen H. (J Biol Chem, 2000)
Saccharomyces cerevisiae selectively uses good nitrogen sources (glutamine) in preference to poor ones (proline) by repressing GATA factor-dependent transcription of the genes needed to transport and catabolize poor nitrogen sources, a physiological process designated nitrogen catabolite repression (NCR). We show that some NCR-sensitive genes (CAN1, DAL5, DUR1,2, and DUR3) produce two transcripts of slightly different sizes. Synthesis of the shorter transcript is NCR-sensitive and that of the longer transcript is not. The longer transcript also predominates in gln3Δ mutants irrespective of the nitrogen source provided. We demonstrate that the longer mRNA species arises through the use of an alternative transcription start site generated by Gln3p-binding sites (GATAAs) being able to act as surrogate TATA elements. The ability of GATAAs to serve as surrogate TATAs, i.e. when synthesis of the shorter, NCR-sensitive transcripts are inhibited, correlates with sequestration of enhanced green fluorescent protein (EGFP)-Gln3p in the cytoplasm in a way that is indistinguishable from that seen with EGFP-Ure2p. However, when the shorter, NCR-sensitive DAL5 transcript predominates, EGFP-Gln3p is nuclear. These data suggest that the mechanism underlying NCR involves the cytoplasmic association of Ure2p with Gln3p, an interaction that prevents Gln3p from reaching it is binding sites upstream of NCR-sensitive genes.